The effect of a learning program based on specific exercises on the skill performance and accuracy of the drive forehand and the smash in badminton - رحال, يارا; رشا ضويا; نوري بركات (Latakia University Journal -Medical Sciences Series, 2024)
The research aimed to know the effect of a learning program using specific exercises on the level of skill performance and accuracy of the forehand drive and forehand smash in badminton, in addition to knowing the correlation between the level of skill performance and accuracy during the performance of the two skills in post-test. Evaluation forms for skill performance were used after they were presented to the arbitrators and accuracy was tested before and after implementing the learning program. The learning program was implemented for 6 weeks (2 weeks for the forehand drive, 2 weeks for the forehand smash, and 2 weeks for a combination of the two), at a rate of 3 weekly sections, and the duration of each section was 90 minutes, divided into parts (an introductory part, a main part, and a closing part). The subjects included 8 male students from the Faculty of Physical Education at Tishreen University, whose ages ranged from 23±2 years. The results of the study showed that the learning program using specific exercises contributed significantly to raising the level of skill performance and accuracy in the post-test. The statistical results also showed a positive correlation between the level of skill performance and accuracy of the post-test among the subjects.